Neuro-Behçet Disease and Autoinflammatory Disorders - Miller, Julie J.; Venna, Nagagopal; Siva, Aksel (Seminars in Neurology, 2014)
Misregulation of innate immunity leads to autoinflammation. Behçet disease is an autoinflammatory condition involving recurrent attacks of inflammation in skin, eyes, joints, and even the nervous system. The etiology may involve vascular inflammation. Central nervous system involvement in neuro-Behçet disease (NBD) comes in the form of parenchymal NBD or nonparenchymal NBD. The parenchymal form has a predilection for the brainstem, diencephalon and cerebral hemispheres, and represents a meningoencephalitis thought to be related to small vessel vasculitis. Cerebral venous sinus thrombosis, arising from a vasculitic process of large veins, comprises the majority of vascular NBD cases. The rarer monogenetic autoinflammatory syndromes are characterized by periodic fever, and typically present in the pediatric population. Neurologic involvement in these syndromes typically presents in the form of an aseptic meningitis. Treatment of autoinflammatory disorders involves immune modulation with corticosteroids, disease-modifying antirheumatic medications, and increasingly antibodies targeting cytokines like tumor necrosis factor α and interleukin 1.
Keywords: neuro-Behçet; autoinflammatory syndromes; neurologic disease; cerebral venous thrombosis; vasculitis